ACM: a new index to measure the digital divide. (9th December 2008) - Brandtweiner, Roman; Kerschbaum, Johann; Donat, Elisabeth
In developed countries, access to the internet has become, at least hypothetically, possible for everybody. Although access is a precondition for usage, it does not automatically lead to usage. More sophisticated measures are needed to explain the persistent number of non-users. In our paper a new index measure is developed. Based on a representative survey in Austria (N = 529), we reconstruct the DDIX of Selhofer and Husing (2002). Our critique of this index is then used to develop a new index. We argue that, in addition to access, skills and motivation are important components for new internet users.